Pelatihan Budidaya Magot sebagai Solusi Pengelolaan Sampah Organik Berbasis Komunitas di Desa Gadingsari: Indonesia - Purwiandono, Gani; Safitri, Indah; Kania Chairunisa Hamdani, Kanza (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Household organic waste management remains a major challenge in Gadingsari Village, Sanden District, Bantul Regency. Due to low awareness and limited use of waste processing technologies, residents often burn or improperly dispose of organic waste. This community service program aimed to introduce maggot (Black Soldier Fly) cultivation as an innovative, environmentally friendly, and economically beneficial solution. The program was implemented using a Community Based Research (CBR) approach, consisting of four main stages: laying the foundation, planning, information gathering and analysis, and acting on findings. Participatory education and training were conducted to enhance the community’s capacity to manage organic waste as a productive resource. Evaluation results showed an increase in knowledge and skills, along with active community involvement. This initiative is expected to be integrated into the future Waste Processing Facility (TPST 3R) and serve as a replicable model for other villages. Overall, the program contributes to improving environmental quality and promoting sustainable community well-being.